The genus Pseudo-nitzschia (Bacillariophyceae) in Malaysia, including new records and a key to species inferred from morphology-based phylogeny - Teng, sing Tung; Chui, Pin Leaw; Hong, Chang Lim; Po, Teen Lim (Walter de Gruyter GmbH, 2013)
Species of the diatom Pseudo-nitzschia are known to produce domoic acid that is responsible for amnesic shellfish poisoning (ASP). To investigate the potential risk of ASP and species occurrence of toxic or potentially toxic Pseudo-nitzschia in Malaysian waters, plankton samples were collected from 17 locations. Samples were examined through transmission electron microscopy. Species of Pseudo-nitzschia were identified on the basis of the frustule morphology and morphometric measurements. Twentytwo well-described species were recorded, of which 14 are new records for Malaysia. A new morphotype, closely resembling species in the pseudodelicatissima complex, was also discovered. The morphotype differs from other species in the complex by its lower densities of fibulae and striae. Nine of the species have previously been associated with ASP events worldwide. Our study recorded for the first time high species richness of Pseudo-nitzschia in the confined coasts of Malaysia. In addition, we performed a morphology-based phylogeny and proposed a key to Pseudo-nitzschia species, with a special emphasis on the poroid structure of the striae, to aid in species identification.